Assessing the vulnerability of buildings to floods in the lower sector of Slănic River. Case Study of Cernăteşti village, Buzău County, Romania. Issue 1 (1st April 2022) - Costache, R; Popescu, C; Barbulescu, A
Abstract: Assessing the vulnerability of buildings is very important to determine the settlements affected by floods since authorities can take measures before actual flooding takes place. The present research aims to identify areas affected by flooding in Cernăteşti. The village is located in an area where floods are favored by the elongated shape of the catchment, the horizontal slope, relatively small distance between the hills bordering the valley, water accumulation resulting from flash floods formed upstream, and heavy local rainfall. Field observations, GIS techniques, and mathematical calculations have been used in this research. Flood simulations have been made to determine the degree (number of houses and roads affected, estimated losses in lei) of impact at flows with different probabilities of exceedance (10%, 5%, 2%, and 1%). Depending on the exposure, calculated using factors like distance from the river or construction material, the buildings on the left bank of Slănic are more affected and the flooded area is more extensive. Buildings in the south-eastern, north-eastern, and north-western parts of the flooded area are highly vulnerable, but most of the other settlements are less vulnerable.